Utilization of biochar and local available feed resource for mitigation methane emission and increasing the growth in local "yellow" cattle : - Phongphanith, Sengsouly (Can Tho University, 2017)
Contents: Paper1. Effect of water spinach (Ipomoea aquatica) and cassava leaf meal (manihot esculenta Crantz) with or without biochar on methane production in an in vitro rumen incubation using esiled or dried cassava root meal sa source of carbohydrate.Paper 2.l Effect of rice wine distiller's by product, biochar and sweet or bitter cassava leaves on gas production in an in vitro incubation using ensiled cassava root as substrate. Paper 3. Effect of rice-wine distiller's by product and biochar on growth performenceand methane emissions in local "Yellow" cattle fed ensiled cassava root, urea, cassava foliage and rice straw.